Effect of cinnamon (Cinnamomum zeylanicum) Essential Oil as an alternative to Antibiotic Growth Promoter in Broilers - Solanki, Devasi M.; Dave, Chandrakant J.; Bhanderi, Bharat B.; Sheth, Aaftabhussain L.; Ghodasara, Dinesh J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present investigation was planned to evaluate the effects of cinnamon oil as an alternative to antibiotic growth promoter in broilers. A total of 144 broiler chicks were randomly allocated to six experimental groups, each consisted of four replicates and each replicate consisted of six chicks. The experimental groups were (I) basal diet; (II) basal diet + chlortetracycline @ 1 g/kg feed; (III) basal diet + cinnamon oil @ 400 mg/kg feed; (IV) basal diet + E. coli @ 1.0 mL (1.5×108 CFU/mL) orally on 14th day; (V) basal diet + chlortetracycline + E. coli; and (VI) basal diet + cinnamon oil + E. coli. The study was conducted for 28 days. There was significant decrease in E. coli counts (Log10 CFU/g) in precaecal-caecal digesta of birds supplemented with cinnamon oil (group III) and chlortetracycline (group II) as compared to other groups on 21st and 28th day of experiment. The caecal average bacterial count of E. coli in birds of group-V and group-VI on 7th day post-infection was significantly higher than group-I, while significantly lower than group-IV. However, on 14th day post-infection the caecal average bacterial count of E. coli in birds of group-V and group-VI was significantly lower than group-I. It was noticed that supplementation of chlortetracycline was more effective than cinnamon oil as an antibacterial agent. There was significant increase in one or all measurements, such as villi height, villi width or villi height to crypt depth ratio in the duodenum, jejunum and ileum of birds supplemented with cinnamon oil (group III) as compared to the birds of other groups on 21st and 28th day of experiment. The overall gross and histopathological lesions in birds of E. coli infected groups were mild degenerative changes in small intestine on 21st day of sacrifice. Based on foregoing observations, it can be summarized that the cinnamon oil can be used by the poultry farmers as an alternative to antibiotic growth promoter.